Aesthetics and world politics - Bleiker, Roland (Houndmills, Basingstoke, Hampshire ; New York : Palgrave Macmillan, 2009)
"This book presents one of the first systematic assessments of aesthetic insights into world politics. It examines the nature of aesthetic approaches and outlines how they differ from traditional analysis of politics. The book explores the potential and limits of aesthetics through a series of case studies on language and poetics"--Provided by publisher
The aesthetic turn in international political theory -- Art after 9/11 -- The sublime nature of global politics -- Poetic world politics -- Poetry after Auschwitz -- Poetic resistance to Cold War politics -- Come see the blood iin the streets -- Poetics and the politics of memory -- The poetic search for identity and community
Includes bibliographical references and index
Keywords: Aesthetics -- Political aspects; World politics; Political poetry